Role of cultural practices in the management of Septoria leaf spot of tomato - S.K. SUGHA, SUMAN KUMAR and (Indian Phytopathology, 2002)
Field trials were conducted at the experimental farm of the Department of Plant Pathology, H.P. Krishi Vishvavidyalaya, Palampur, Himachal Pradesh, India, during two consecutive kharif seasons, to determine the effect of cultural practices (spacing,staking, defoliation and intercropping) on the development of Septoria leaf spot of tomato (cv. Roma) caused by S. lycopersici. A progressive increase in row spacing corresponded to a decrease in the severity of Septoria leaf spot. Row spacings of 45 and 60 cms did not differ significantly recording 57.6 and 57.8% disease incidence, respectively, after 3 weeks. The disease developed slowly in widely spaced (90 cm) tomato resulting in 28.2% disease incidence after 3 weeks. Tomato plants which were staked with the lower leaves defoliated developed less disease (35.9% after 3 weeks) compared with staked but undefoliated plants (67.2%). Similarly, defoliated but unstaked tomato also showed less disease development (57.5%) than unstaked and undefoliated plants (76.2%). Among the different crops (Phaseolus vulgaris, toria (Brassica campestris var. toria) and maize), tomato intercropped with maize, either in single or double rows, developed less disease than when intercropped with Phaseolus vulgaris or toria. Tomato alternating with single rows of the intercrops developed more disease in comparison to two rows of these crops.